Recombination of bacteriophage phi X174 by the red function of bacteriophage lambda. - Munekiyo, R (1979)
Recombination of bacteriophage phi X174 was effectively promoted when the Red function of lambda was supplied by either co-infection with lambda or induction of lambda lysogens. Mutations in red alpha and red beta genes of lambda abolished recombination nearly completely, whereas a mutation in gam gene reduced it only slightly. The Red-promoted recombination of phi X174 occurred in recA, recB, and polA mutants as well as in wild-type strains of Escherichia coli. It was further stimulated when phi X174 mutants were irradiated with UV light before infection.